TEKNIK PENERJEMAHAN DEIKSIS DARI BAHASA INDONESIA KE DALAM BAHASA INGGRIS - HASANAH, LULUK ULFA (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2018)
This research aims to obtain an outline of the translation techniques used in the translation of deixis. The focus of it is on the techniques of deixis translation that used by translators. The qualitative approach used in this research with content analysis method. There are 284 data on the deixis translation which shows the use of translation techniques as a major problem in this. The result of this is found nine types of the translation techniques, namely the technique of generalization, amplification, borrowing, literal translation, linguistic amplification, particularisation, reduction, modulation, and transposition. The type of translation with literal translation techniques occupies the most widely used of the translator. That is, in the deiksis translation, translators use more word-by-word translation, becouse deixis occupies more units of words or phrases in a sentence. Keywords: deixis, translation, the translation techniques, the translation techniques of deixis